Detection of unexpected coronavirus disease (COVID-19) involvement in lung bases on abdominal CT of patients presenting with abdominal symptoms - Özgül, Esra; Kaya, Furkan; Korkmaz, Derya (Journal of Surgery and Medicine, 2020)
Aim: Coronavirus disease 2019 (COVID-19) can present with nonspecific abdominal symptoms. The aim of this study is to emphasize the importance of detecting lung basis involvement on abdominal computed tomography (CT) in patients hospitalized with abdominal complaints without known COVID-19 disease. Methods: CT images of 250 patients who underwent abdominopelvic CT scan due to various abdominal complaints were retrospectively evaluated. Inclusion criteria included patients presenting with primary abdominal complaints without respiratory symptoms, who had suspicious COVID-19 CT findings on lung basis. COVID-19 was not among the differential diagnoses of these patients at the time of admission. Results: Among 240 patients, twelve (8 females, 4 males, aged 30-69 years) had suspicious findings of COVID-19 on lung bases. Presenting complaints were abdominal pain (n=7), lack of appetite (n=5), diarrhea (n=7), vomiting (n=3), nausea (n=4) and gastric pain (n=1). Lung base CT findings included ground-glass opacities (100%), which were peribronchovascular (66.6%), bilateral (91.6%), peripheral (91.6%), or multifocal (58.3%). Cases were confirmed with laboratory testing. Conclusion: Considering that some patients present with nonspecific abdominal complaints, identifying the characteristic signs of COVID-19 incidentally in the visualized part of the lung basis on abdominal CT is important for early diagnosis, the protection of health professionals, and in reducing the spread of disease.